NON-PHARMACOLOGICAL INTERVENTIONS FOR TREATING SYMPTOMS OF KNEE OSTEOARTHRITIS IN OVERWEIGHT OR OBESE PATIENTS; A REVIEW - Rafiq, Muhammad Tariq; A Hamid, Mohamad Sharif; Hafiz, Eliza (Journal of Postgraduate Medical Institute, 2021)
Objective: To explore the current literature on the effects of non pharmacological interventions on weight reduction, knee pain and function in patients with knee osteoarthritis who are overweight or obese. Methodology: Three databases; Web of Science, PubMed Central and ScienceDirect were searched using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search terms used were "overweight and obese knee OA Patients, Treatment, Strengthening exercises, Range of motion exercises, High intensity exercises or Mobile health (mHealth)". Only articles written in English language and published in peer reviewed journals from August, 2008 to September, 2018 were searched. Out of 2838 articles identified, only 10 were considered relevant. Results: The most effective intervention that showed improvement of knee pain and function was strengthening exercise. The two most effective interventions for weight reduction, among patients with knee osteoarthritis who were overweight or obese, were caloric restriction alone and diet intervention combined with the exercise program. Dietary intervention alone also reported a loss of fat significantly, when compared to exercise group. Conclusion: Strengthening exercise played a vital role in relieving knee pain and improving function. A caloric restriction diet was found helpful in reducing weight. Combination of diet and exercise was found effective in reducing weight and improving knee pain.